Medical practitioners as 'Good Samaritans': the emerging duties and liabilities under the Shari'ah and civil law - Jahn Kassim, Puteri Nemie; Shahul Ikram, Nur Adlin Hanisah (USIM Press, Universiti Sains Islam Malaysia, 2018)
The ability to cure and alleviate harm has made medical practitioners vulnerable to expectations of the society. Society expects medical practitioners to unhesitatingly render assistance to those who are injured and in distress. In other words, medical practitioners are expected to act as ‘Good Samaritans’ who unselfishly comes to the aid of those who suffer harm, even though they are strangers. Such altruistic behavior has been incessantly reiterated in various provisions in the Holy Qur’an. In Surah Al-Maidah, verse 32, Allah swt stated to the effect “…and if anyone saved a life, it is as if he had saved the life of the whole mankind.” Further, in Surah Al-Nisa’, verse 36, Allah swt stated to the effect “…show kindness to parents, kinfolk, orphans, and those who are in need, neighbours who are near as well as neighbours who are strangers…”. The growing demands by the society for medical practitioners to act as ‘Good Samaritans’ have also triggered the enactment of various laws around the globe imposing criminal sanctions for failure to render assistance to the injured. In understanding these emerging responsibilities of medical practitioners, this paper seeks to discuss the duties and liabilities of medical practitioners when acting as Good Samaritans under the Shari’ah as well as the Civil Law. This paper will also examine the global development of ‘Good Samaritan Laws’ which offers legal protection for medical practitioners from being prosecuted for unintentional injury or wrongful death, with the aim of encouraging the engagement of such altruistic behaviour invariably.